2007
DOI: 10.1111/j.1461-9563.2007.00336.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of a geographic information system to explore spatial variation in pathogen virulence and the implications for biological control of locusts and grasshoppers

Abstract: 1 In a previous study, we developed a model to predict the effects of temperature on performance of a fungus-based biopesticide for controlling locusts and grasshoppers. Currently, the model is limited to predicting rate of mortality after a spray application at site-specific locations. The aim of the present study is to enhance the utility of this model by linking it with meteorological station data in a geographic information system (GIS) framework to investigate the spatial variation in the performance of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 31 publications
2
37
0
1
Order By: Relevance
“…It has a role in interpreting patterns of mortality after application, providing locust control officers with real-time guidance as to when to expect substantial levels of mortality, and for prospective analysis to identify candidate targets for biocontrol and optimize use strategies. We are currently working to increase the utility of this model by linking with meteorological station data in a Geographic Information Systems framework to enable area-wide applications ( Klass et al , 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has a role in interpreting patterns of mortality after application, providing locust control officers with real-time guidance as to when to expect substantial levels of mortality, and for prospective analysis to identify candidate targets for biocontrol and optimize use strategies. We are currently working to increase the utility of this model by linking with meteorological station data in a Geographic Information Systems framework to enable area-wide applications ( Klass et al , 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…More fundamentally, although numerous modelling studies (including some excellent recent work informing contemporary control strategies 89,90 ) integrate aspects of the effects of environmental temperature, none includes the possible effects of temperature on vector resistance, which could be responsible for much of the variation in vector competence over time and space. Modelling work quantifying the spatial and temporal variation in the susceptibility of locusts and grasshoppers to fungal insect pathogens used in biological control provides an interesting illustration of the practical value of understanding temperature-dependent resistance and virulence 91,92 .…”
Section: Discussionmentioning
confidence: 99%
“…This is especially true for ectotherms where ambient conditions constrain the physiological temperatures of both host and pathogen (Carruthers et al 1992;Blanford & Thomas 1999Jackson & Tinsley 2002;Blanford et al 2003;Klass et al 2007;Laine 2008;Lazarro et al 2008). Several experimental studies have now demonstrated an effect of temperature on the susceptibility and behaviour of ectotherm hosts and/or the virulence of their pathogens (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, the functional mechanisms underlying these effects and their potential to affect the outcomes of infections under natural conditions are not well understood (Carey et al 1999;Jackson & Tinsley 2002). A clearer understanding of the links between environmental factors and the outcomes of host-pathogen interactions will probably provide valuable insights into host-pathogen coevolution and epidemiology, as well as more fundamental aspects of the ecology and evolution of interspecific interactions (Lambrechts et al 2006;Klass et al 2007). Given the potential impact of ongoing climate change on disease risk for humans (McMichael 2006;Estrada-Pena 2009) and other organisms (e.g.…”
Section: Introductionmentioning
confidence: 99%